Peran Pemerintah dalam Mengatasi Anak Putus Sekolah di Kelurahan Madale Kecamatan Poso Kota Utara Kabupaten Poso - Saputra, Muh. Wahyu; Gobel, Lisda Van; Antu, Yahya (Ideas Publishing, 2025)
The phenomenon of increasing numbers of school dropouts in Madale Village, influenced by socio-economic factors, as well as less than optimal government intervention, has become an urgent need to be studied in order to evaluate the role of the government in effectively overcoming this problem. This study aims to determine and describe the role of the government in overcoming school dropouts in Madale Village, North Poso City District, Poso Regency. This study uses a qualitative descriptive approach with data collection methods in the form of in-depth interviews, direct observation, and documentation. The results of the study indicate that supporting facilities for school dropouts are still less than optimal, such as uneven program realization, low community access to information and educational assistance. The government as a motivator is also still less than optimal, this is because the implementation and encouragement of the government are considered not optimal and have not been evenly felt by children who have dropped out of school. In addition, the government as a mobilizer is considered still not optimal, this is because the government has not been able to mobilize elements of society or community leaders to help overcome the problem of school dropouts. This study suggests that the active role of the village government is very much needed to reduce the number of school dropouts through a more effective and sustainable facilitation, motivation, and mobilization approach.